Transformasi Perluasan Makna Kerugian Keuangan Negara Atas Anak Usaha Bumn - Rifqi Aziz, Mohammad (LPPM Universitas Ekasakti Padang, 2024)
In its journey, the concept of state finance, especially the development of the concept of separation of State Finance and State-Owned Enterprises (BUMN), has undergone a fairly progressive transformation. The idea of separating state assets from BUMN assets has implications for affirming that capital participation from the government to the state budget does not make BUMN assets become state-owned assets, so that losses experienced by BUMN are not state losses. However, the definition of separation of wealth has not been strictly applied to SOE subsidiaries, resulting in confusion about the financial status of SOE subsidiaries if they experience losses.